ECOTOURISM: NURTURING SUSTAINABLE TRAVEL FOR A GREEN FUTURE - Mirxadjayeva Malika Muzaffarovna (Web of Journals Publishing, 2024)
Ecotourism, characterized by responsible travel that fosters environmental conservation and promotes local community development, has emerged as a crucial force in the global tourism industry. This scientific article delves into the multifaceted dimensions of ecotourism, examining its principles, impacts, challenges, and future prospects. By synthesizing existing research and drawing upon case studies, this article aims to contribute to the understanding of how ecotourism can be a catalyst for sustainable practices, biodiversity preservation, and socio-economic upliftment.